Hospital Resource Management Interoperability for Pandemic Management: Research Development - Riky Perdana; Dwi Kartini; Yudi Azis; Umi Kaltum (International ABEC, 2021)
Pandemic is a medical disaster that affects almost all countries in the world. The front line for handling this pandemic is none other than the hospital as a service provider and the government as the coordinator. Despite the maximum efforts of each party, gaps are still found between the capacity of medical facilities and the large number of requests for patients. One of the shortcomings observed by the researchers was that there was no information exchange protocol that allowed the government and all participating hospitals to exchange information on the actual availability of resources, which allowed all patients to be directed quickly to health facilities that still had service capacity. This study attempts to design a hospital resource information exchange protocol that can be used to handle the distribution of pandemic patients more quickly and accurately. The research method used is the Expert System Development Life Cycle. The testing conducted with White Box Testing Method which done by the developer. The results of this study are in the form of 3 things, including: 1. Cross-hospital interoperability network topology that can be mediated by the government or certain agents, 2. Standard data structures that can be transmitted via a web service, 3. Standard Operating Procedures that can guide all participants to perform exchange the following resource data with patient distribution.